LEARNING METHODS TO BOOST THE MOTIVATION OF ELEMENTARY SCHOOL STUDENTS IN BELITUNG - Azizah, Siti Nur; Pramana, Jelita Nurindria; Parasti, Meita Putri; Aryanti, Ryandra Sakhaputri; Rustandi, Putri Rizkiani; Masrifatul, Nujum; Azkiana, Zuhra; Hasan, Nurlia Marwaty; Rahman, Husna Annisa (SMARTINDO, 2023)
Education is a means of learning to improve the quality of human resources, so every country is competing to improve the quality of its people by providing qualified educational facilities, especially for children in elementary schools. However, not all elementary school students have high motivation to study and achieve their goals. Due to the high level of saturation in subjects. This activity is located in Elementary School 16 Sijuk, Belitung Regency, with 120 students divided into five classes. The method of carrying out activities is divided into several stages and classes coordinated by one person in charge of activities in that class. This service provides innovation to teach students the educational game method. In addition, this service provides understanding related to professions in Indonesia to increase students' interest in learning and achieving their goals with the Dream Tree method. After this activity, elementary school students became more cheerful and excited to take part in lessons at school, even for relatively complex material such as mathematics and English. These findings show that elementary school students need regular subject matter refreshments to reduce their stress levels and boredom in learning. Thus, the subjects the teacher teaches become more effective and efficient for them.